2006
DOI: 10.1051/0004-6361:20065696
|View full text |Cite
|
Sign up to set email alerts
|

The stellar content of the XMM-Newton bright serendipitous survey

Abstract: Context. The comparison of observed counts in a given sky direction with predictions by Galactic models yields constraints on the spatial distribution and the stellar birthrate of young stellar populations. The XMM-Newton Bright Serendipitous Survey (XBSS) is an unbiased survey that includes a total of 58 stellar sources selected in the 0.5-4.5 keV energy band, having a limiting sensitivity of 10 −2 cnt s −1 and covering an area of 28.10 sq deg. Aims. We present the results of analysing the stellar content of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 54 publications
4
40
0
Order By: Relevance
“…The optical and X-ray properties of the Galactic population are discussed in López-Santiago et al (2007). Previous X-rays spectral analyses of parts of the XBS sample have already been reported in previous works.…”
Section: The Xbs Agn Samplementioning
confidence: 90%
“…The optical and X-ray properties of the Galactic population are discussed in López-Santiago et al (2007). Previous X-rays spectral analyses of parts of the XBS sample have already been reported in previous works.…”
Section: The Xbs Agn Samplementioning
confidence: 90%
“…In general, the coronal plasma exhibits a temperature gradient that cannot be studied using low-resolution X-ray spectra (although see Robrade & Schmitt 2005). Nevertheless, it has been shown that the dual-temperature nature of the fits may represent an intrinsic property of the coronal spectra of moderately active late-K and M stars (Schmitt et al 1990;Briggs & Pye 2003;López-Santiago et al 2007). In this scenario, the third (higher) temperature required to fit the hard tail of the X-ray spectrum is understood to be present only during flare-like events.…”
Section: General Propertiesmentioning
confidence: 99%
“…Because of this and their ubiquity, late-type stars are excellent tracers of the Galactic potential (Bochanski et al 2007). Distinguishing between young and old stars is then crucial to an understanding of the kinematics of the Galaxy and of stellar formation history in our neighborhood (López-Santiago et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In this new era of Virtual Observatory and extensive photometric databases and catalogs, the compilation of spectroscopic data is important for the purpose of constraining the properties of different astronomical objects, in particular, of stars (e.g. Sciortino et al 1995;Takeda et al 2007;Micela et al 2007;López-Santiago et al 2007;Klutsch et al 2008;López-Santiago et al 2009). The utility of substantial spectroscopic compilations has been demonstrated in the past by various groups.…”
Section: Introductionmentioning
confidence: 99%